HUBUNGAN RELIGIUSITAS DAN REGULASI EMOSI TERHADAP RESILIENSI PADA DEWASA AWAL KORBAN GHOSTING - Ratna Duhita Pramintari; Hanafia Amalia; Siti Nurhidayah (Fakultas Psikologi Universitas Buana Perjuangan Karawang, 2022)
The purpose of this study was to determine the relationship between religiosity and emotional regulation on resilience in early adulthood ghosting victims. This research is a quantitative research. Participants in this study were determined using a sampling quota of 123 early adult student participants who were ghosted victims at the